2013
DOI: 10.1159/000346683
|View full text |Cite
|
Sign up to set email alerts
|

Human Amnion Epithelial Cells Reduce Fetal Brain Injury in Response to Intrauterine Inflammation

Abstract: Intrauterine infection, such as occurs in chorioamnionitis, is a principal cause ofpreterm birth and is a strong risk factor for neurological morbidity and cerebral palsy. This study aims to examine whether human amnion epithelial cells (hAECs) can be used as a potential therapeutic agent to reduce brain injury induced by intra-amniotic administration of lipopolysaccharide (LPS) in preterm fetal sheep. Pregnant ewes underwent surgery at approximately 110 days of gestation (term is approx. 147 days) for implant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 41 publications
(56 reference statements)
4
67
1
Order By: Relevance
“…Prior studies exploring the protective effects of hAECs in lamb models of inflammation-induced lung and brain injury have clearly demonstrated their anti-inflammatory and reparative effects over a period of 1 week [19,21]. The lack of such effects in our study is probably due to the timing of cell administration or the short duration of the experiment.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Prior studies exploring the protective effects of hAECs in lamb models of inflammation-induced lung and brain injury have clearly demonstrated their anti-inflammatory and reparative effects over a period of 1 week [19,21]. The lack of such effects in our study is probably due to the timing of cell administration or the short duration of the experiment.…”
Section: Discussionmentioning
confidence: 67%
“…Fetal lung inflammation induced by intra-amniotic lipopolysaccharide injection is attenuated by hAEC administration [19], and ventilation-induced abnormal lung remodelling in fetal sheep is also reduced [20]. The neuroprotective capacity of hAECs has not been extensively studied; however, hAECs are capable of reducing brain inflammation and injury in preterm fetal sheep exposed to intra-amniotic lipopolysaccharide [21]. …”
Section: Introductionmentioning
confidence: 99%
“…This can result in increased number of infiltrating inflammatory cells, activation of resident microglia (which causes local amplification of proinflammatory cytokines), increased oxidative stress, and subsequent diffuse white matter gliosis within the periventricular white matter, subcortical white matter, and corpus callosum (Figure 4) (4,58,59). This brain inflammatory environment, notably an increase in activated microglial cells, is a prominent feature of neuropathologies and can be correlated with brain cell death (60). As a clinical correlate, diffuse "microstructural" white matter injury within the corpus callosum in infants born at <33 wk gestation is clinically associated with poor cognitive function at 19 years of age (61).…”
Section: Inflammatory Consequences Of the Initiation Of Respiratory Smentioning
confidence: 99%
“…They express neural genes and secrete multiple neurotransmitters [66,67]. Only one study to date has demonstrated neuroprotective and anti-inflammatory responses after intravenous and intratracheal hAEC administration in the neonatal brain following inflammation-induced brain injury in fetal sheep [68]. Given that hAEC are able to protect the preterm lung from in utero ventilation- and inflammation-induced lung injury [63,64], and that they protect the brain from in utero inflammation-induced damage [68], they may also have the potential to protect against ventilation-induced brain injury as a postnatal treatment.…”
Section: Postnatal Therapiesmentioning
confidence: 99%
“…Only one study to date has demonstrated neuroprotective and anti-inflammatory responses after intravenous and intratracheal hAEC administration in the neonatal brain following inflammation-induced brain injury in fetal sheep [68]. Given that hAEC are able to protect the preterm lung from in utero ventilation- and inflammation-induced lung injury [63,64], and that they protect the brain from in utero inflammation-induced damage [68], they may also have the potential to protect against ventilation-induced brain injury as a postnatal treatment. We observed an apparent beneficial effect of hAEC on brain inflammation as a result of high V T ventilation; hAEC (administered both intravenously and intratracheally) reduced microgliosis and vascular protein extravasation in the brain 2 h after of ventilation onset [9].…”
Section: Postnatal Therapiesmentioning
confidence: 99%